Model of Student E-Loyalty Formation Through E-Service Quality and E-Satisfaction - Salamatun Asakdiyah; Jason Keith Bonaga; Indro Prastowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The increasingly intense competition in higher education services is a major concern for universities to survive. One of the strategies universities can do to survive is the formation of student E-Loyalty through increasing student E-Service Quality and E-Satisfaction. This study aims to examine the effect of E-Service Quality on student E-Satisfaction, the effect of E-Satisfaction on student loyalty and the effect of E-Service Quality on student E-Loyalty mediated by student E-Satisfaction. In addition, the results showed that E-Service Quality affects student E-Loyalty which is mediated by student E-Satisfaction. The results of this research prove that the model of forming student E-Loyalty can be achieved through student E-Service Quality can be achieved through E-Service Quality and E-Satisfaction of students of the Ahmad Dahlan University Faculty of Economics and Business Management Study Program. The sample was determined by convenience sampling and purposive sampling methods. Data collection is done by giving a list of questions to respondents containing E-Service Quality, student E-Satisfaction and student E-Loyalty. The analytical tool used is Partial Least Square (PLS). Keywords : E-Service Quality, E-Satisfaction, E-Loyalty